The Effect of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on Firm Value With Financial Performance as an Intervening Variable Among Manufacturing Companies Listed on The Indonesian Stock Exchange - Rasti Rezkita; Hajrah Hamzah; Azwar Anwar (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the effect of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on firm value with financial performance as an intervening variable in manufacturing companies in the primary consumer goods sector listed on the IDX for the period 2022–2024. This study uses second-ary data obtained through documentation, with a sample of 67 companies select-ed using purposive sampling. Data analysis was conducted using descriptive sta-tistics and PLS analysis with the PLS-SEM method via the SmartPLS software. The results of this study indicate that GCG has a significant positive effect on financial performance. CSR does not have a significant effect on Financial Per-formance. Financial Performance has a significant positive effect on Company Value. GCG does not have a significant effect on Company Value. CSR has a significant positive effect on Company Value. Financial Performance was found to mediate the effect of GCG on Company Value, but was not found to mediate the effect of CSR on Company Value.